Detection of herpes simplex virus in oral tongue squamous cell carcinoma - Koivikko, Tiina; Rodrigues, Priscila Campioni; Vehviläinen, Mari; Hyvönen, Petra; Sundquist, Elias; Arffman, Riikka K.; Al-Samadi, Ahmed; Välimaa, Hanna; Salo, Tuula; Risteli, Maija (Frontiers in Pharmacology, 2023)
Oral tongue squamous cell carcinoma (OTSCC) is the most common cancer of the oral cavity. Contradictory results have been observed on the involvement of herpes simplex virus 1 (HSV-1) in oral squamous cell carcinomas. Here, we aimed to study the predominance of HSV-1 or HSV-2 in oral HSV infections and to investigate the presence of HSV-1 in OTSCC and its effect on carcinoma cell viability and invasion. The distribution of HSV types 1 and 2 in diagnostic samples taken from suspected oral HSV infections was determined from the Helsinki University Hospital Laboratory database. We then analysed 67 OTSCC samples for HSV infection using immunohistochemical staining. We further tested the effects of HSV-1 using six concentrations (0.00001 to 1.0 multiplicity of infection [MOI]) on viability and two concentrations (0.01 and 0.1 MOI) on invasion of highly invasive metastatic HSC-3 and less invasive primary SCC-25 OTSCC cell lines using MTT and Myogel-coated Transwell invasion assays. Altogether 321 oropharyngeal samples were diagnosed positive for HSV during the study period. HSV-1 was the predominant (97.8%) HSV type compared with HSV-2 (detected in 2.2% of samples). HSV was also detected in 24% of the OTSCC samples and had no association with patient survival or recurrence. OTSCC cells were viable even after 6 days with low viral load (0.00001, 0.0001, 0.001 MOI) of HSV-1. In both cell lines, 0.01 MOI did not affect cell invasion. However, 0.1 MOI significantly reduced cell invasion in HSC-3 cells. HSV-1 infection is predominant compared with HSV-2 in the oral cavity. HSV is detected in OTSCC samples without clinical significance, and OTSCC cell survival or invasion was not affected at low doses of HSV-1.